Human Resource Management Development Strategy at RPK Omah Laundry Prapen: Strategi Pengembangan Manajemen Sumber Daya Manusia Pada RPK Omah Laundry Prapen - Windi Uneny; Raden Johnny Hadi Raharjo (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
RPK (Rumah Padat Karya) Omah Laundry Prapen is a community based business unit under the Surabaya City Government program that operates in the laundry services sector. RPK Omah Laundry has challenges in human resource management, primarily due to a decline in the number of employees. This community service initiative aims to assist in designing and implementing HR development strategies through needs analysis, performance evaluation, and a participatory approach. The activities involved include field observations, interviews, as well as the development of Standard Operating Procedures/SOP and performance evaluation systems. The results demonstrate that structured HR management strategies, such as work shift rotation, targeted training, and regular performance assessments, can enhance operational efficiency and boost employee motivation.